Crowd Control: Classroom Management and Effective Teaching for Chorus, Band, and Orchestra - Haugland, Susan L. (Rowman & Littlefield Publishers, 2013)
Crowd Control 2nd edition is a nuts-and-bolts manual for teachers of middle and high school performance-based classes such as band, orchestra, and chorus. This practical 'how-to' guide shows teachers, pre-service or experienced, efficient ways to manage large performance-based classrooms. With wit and sage tried-and-true advice, Haugland provides a complete behavior plan as well as concrete ideas for addressing the National Standards, Common Core, assessment, advocacy, and ensemble team building, along with ways to form a professional network. Accessible and indispensable, Crowd Control will become a vital resource in every music teacher's library.